Hubungan Diabetes Mellitus Tipe 2 Dengan Luas Lesi Pada Foto Toraks Penderita Tuberkulosis Di Rumah Sakit Kabupaten Konawe - Muh. Ajib Ardin; Daniel Ruslim (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Tuberculosis (TB) is an infectious disease that can attack various organs, especially the lungs. People with Diabetes Mellitus are more susceptible to tuberculosis infection because there is damage to the function of immune cells. This study was conducted to determine the relationship between Diabetes Mellitus type 2 and the area of lesions in thoracic photos of tuberculosis sufferers at Konawe Hospital. This study used an observational analytical research design with a cross-sectional approach. The results of this study obtained 7.4% of Diabetes Mellitus type 2 patients with Tuberculosis in the broad lesion category and based on the results of the spearman test obtained a value (p = 0.036) (r = 0.405) which means that there is a significant relationship between Diabetes Mellitus type 2 and the area of the lesion in the thoracic photo of tuberculosis sufferers at Konawe Regency Hospital